Executive functioning during prolonged exercise: a fatigue-based neurocognitive perspective - Schmit, C.; Brisswalter, J. (International Review of Sport and Exercise Psychology, 2020)
Despite emotional, technical and endurance implications for athletes` performance, a consensus has yet to be reached to explain the impairment of executive functioning during exercise. In particular, recent research challenges the original assumption of a linear dose-response effect of exercise intensity on cerebral physiology and executive functioning. We propose a fatigue-based neurocognitive perspective of executive functioning during prolonged exercise, suggesting that top-down (cognitive and physical efforts) and bottom-up processes (body sensations) act in parallel of arousing mechanisms to determine cognitive outcomes. In this perspective, executive functioning during prolonged exercise would be dynamical rather than steady (i.e. positively then negatively impacted by exercise) and would be to analyse in regards of exercise termination rather than of exercise intensity.